Genomic analysis of the early COVID-19 pandemic in Haiti reveals Caribbean-specific variant dynamics. - Alexandra Mushegian; Allie Kreitman; Martha I Nelson; Matthew Chung; Christopher Mederos; Allison Roder; Stephanie Banakis; Anne Marie Desormeaux; Nadia Lapierre Jean Charles; Yoran Grant-Greene; Samson Marseille; Katilla Pierre; et al. (PLOS Global Public Health)
Pathogen sequencing during the COVID-19 pandemic has generated more whole genome sequencing data than for any other epidemic, allowing epidemiologists to monitor the transmission and evolution of SARS-CoV-2. However, large parts of the world are heavily underrepresented in sequencing efforts, including the Caribbean islands. We performed genome sequencing of SARS-CoV-2 from upper respiratory tract samples collected in Haiti during the spring of 2020. We used phylogenetic analysis to assess the pandemic dynamics in the Caribbean region and observed that the epidemic in Haiti was seeded by multiple introductions, primarily from the United States. We identified the emergence of a SARS-CoV-2 lineage (B.1.478) from Haiti that spread into North America, as well as evidence of the undocumented spread of SARS-CoV-2 within the Caribbean. We demonstrate that the genomic analysis of a relatively modest number of samples from a severely under-sampled region can provide new insight on a previously unobserved spread of a specific lineage, demonstrating the importance of geographically widespread genomic epidemiology.